Historical Memory and the Representation of History: Forging Connections Between National Historic Sites and Gender History - Brittney Ann Bos (Conserveries Mémorielles)
The relationship between National Historic Sites and gender history has, up to this point, rarely been explored. By considering historical memory in terms of its significance as a key methodology to both National Historic Sites and gender history, it is possible to more fully understand the potential relationship between these two areas. Historical memory can be understood as both a theoretical framework and methodology that repositions questions about the past and how it is remembered, both individually and collectively. Historical memory is a significant methodology employed within gender history in order to examine complex questions surrounding the formation of memories and history more generally. It builds upon the feminist methodology of oral history but presents a more complex set of questions that examines the construction of the memory itself. Similarly, historical memory is a key methodology used within heritage conservation as it serves as a significant source of documentation and is useful in the ‘performance’ of history at National Historic Sites. The public presentation of memories is not only a useful method of engaging the public about the past, but also has the power to transform the collective memory of the nation. Based on this connection, historical memory is a useful method of understanding the complex and rarely explored connections between gender history and National Historic Sites. This paper examines the role of historical memory as a theoretical framework and feminist methodology in forging connections between these two areas of historic representations.